Complex integrated method of dynamic meditation with Buddhists' breathing in case of neurotic reactions - V.I. Omelyanenko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to elaborate complex integrated method of psychological influence upon sport dancers in time of training on base of Buddhists' meditation "conscious breathing" for neurotic reactions elimination, professional skill improvement and psycho emotional stability advance. Material : twenty dancers at the age of 40-50 with neurotic reactions participated in the research. At the first stage of the research all the subjects' ability to focus attention at breathing during sports dancing performance was examined. At the second stage training in method of dynamic meditation applied for martial arts of the experimental group of 10 subjects was conducted. Both individual and group training sessions were held. At the third stage the experimental group joined dynamic meditation and breathing at dance performance. At the fourth stage the experimental group's results were compared with the control group's results. Results : at the first stage of the research all the subjects noted difficulties in focusing attention on Buddhists' nasal breathing and dance technique come-down. 3-5 sessions of training in method of dynamic meditation were necessary for the subjects of the experimental group at the second stage of the research. At the third stage of the research all the subjects of the experimental group could control their nasal breathing at dance performance without dance technique come-down. At the fourth stage the comparative evaluation of the results of the experimental and control groups revealed that it was necessary 3-7 sport dance practice sessions for elimination of the neurotic reactions. No such effect was observed in the control group. Conclusions : The results of the research prove that Buddhists' meditation "conscious breathing" may be joined with dynamic meditation successfully. It's impossible to focus attention continuously on breathing at time of sport dance performance. The elaborated technique of the integration of the dynamic meditation and Buddhists' "conscious breathing" provides improvement of dancers' psycho emotional state eliminates neurotic reactions, polishes sports dance performance.